Structural and diversity relationships of a riparian forest in a conservation unit and its buffer zone - Pereira, Kelly Marianne Guimarães; Cordeiro, Natielle Gomes; Santana, Lucas Deziderio; Plazas, Inkamauta Valeda Cerda; Matos, Lisandra Maria Alves; Cabacinha, Christian Dias (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
The aim of the study was to analyze the structure, diversity and heterogeneity of the arboreal component of a Riparian Forest in a Conservation Unit. In addition, to compare the structure of this vegetation with the Mata Ripária of the buffer zone. The study area is located in the Lapa Grande State Park, Minas Gerais State (Brazil). The forest inventory was carried out in the conservation unit and in its buffer zone. As a criterion, all individuals with a DBH ≥ 3 cm were measured, as well as their total height. The phytosociological and floristic parameters of the vegetation were processed, and the extended-correspondence analysis (DCA), cluster analysis of the Horn's similarity and the Jaccard coefficient were performed. We sampled 1,426 individuals in the interior and 944 individuals in the buffer zone. The diversity index of Shannon reached to the conservation unit was 4.61 nats.ind-1, the Pielou equability of 0.85. In relation to the buffer zone, the values of diversity were 3.79 nats.ind-1, equability of 0.82. A significant difference was observed between the diversities of the two areas, with values of t = 10.98 for p <0.001. When realizing the similarity of the plots through Cluster analysis it is observed that the plots did not formed distinctives groups, the DCA showed the formation of strong floristic gradients between the environments. We conclude that there is a heterogeneity between the areas. In addition, the areas of the conservation unit and its buffer zone play a major role for conservation.